Ach Brito - sell or not sell? - Monteiro, João Pedro Azevedo Teixeira Guedes (2018)
This case study is based on a real family business, Ach Brito. The company has more than 100 years of history and is in its 4th Generation. It is a well-known Portuguese firm that has had a stable growth and sells in more than 50 countries. The main focus of this case is on participation selling in a family business context. The case intends to: illustrate how family companies can surpass obstacles and return to a stable path; leading to a discussion regarding capital selling in a family business context; family business decision-making complexity and emotional value impact. Ach Brito’s case is a basis for discussion of family business theoretical content. The case includes a teaching note to beacon the lecture of the case in classroom context. Complementary readings and discussion questions with suggested answers are available with the objective of enhancing the learning process.